Functional characterization and differential expression studies of squalene synthase from Withania somnifera - Gupta, Neha; Sharma, Poonam; Kumar, R. J. Santosh; Vishwakarma, Rishi K.; Khan, Bashir Mohammad (Molecular Biology Reports, 2012)
Squalene synthase (SQS: EC 2.5.1.21) is a potential branch point regulatory enzyme and represents the first committed step to diverge the carbon flux from the main isoprenoid pathway towards sterol biosynthesis. In the present study, cloning and characterization of Withania somnifera squalene synthase (WsSQS) cDNA was investigated subsequently followed by its heterologous expression and preliminary enzyme activity. Two different types of WsSQS cDNA clones (WsSQS1and WsSQS2) were identified that contained an open reading frames of 1,236 and 1,242 bp encoding polypeptides of 412 and 414 amino acids respectively. Both WsSQS isoforms share 99 % similarity and identity with each other. WsSQS deduced amino acids sequences, when compared with SQS of other plant species, showed maximum similarity and identity with Capsicum annuum followed by Solanum tuberosum and Nicotiana tabacum. To obtain soluble recombinant enzymes, 24 hydrophobic amino acids were deleted from the carboxy terminus and expressed as 6X His-Tag fusion protein in Escherichia coli. Approximately 43 kDa recombinant protein was purified using Ni-NTA affinity chromatography and checked on SDS-PAGE. Preliminary activity of the purified enzymes was determined and the products were analyzed by gas chromatograph-mass spectrometer (GC-MS). Quantitative real-time PCR (qRT-PCR) analysis showed that WsSQS expresses more in young leaves than mature leaves, stem and root.
Keywords: Gas chromatograph-Mass Spectrometer (GC-MS); qRT-PCR; Squalene synthase; Withania somnifera

Cloning and sequence analysis of three variants of the gene encoding alkaline xylanase C from the alkaliphilic bacillus sp (NCL 87-6-10) - Sharma, Poonam; Rele, Meenakshi V.; Kumar, Lalitha Sunil (Biochemical Genetics, 2013)
Alkaline xylanase C from the alkaliphilic Bacillus sp. (NCL 87-6-10) has a low molecular weight and alkaline pI and is cellulase-free, properties compatible with its use in the prebleaching of pulp. We report here the cloning and sequence analysis of three variants of the gene encoding xylanase C; xyl C1, xyl C2, and xyl C3. In phylogenetic analysis, the three xylanase C variants clustered into a single group along with other reported alkaline xylanases. Residues contributing to the alkaline pH were present in all three variants. DNA and protein sequence comparison of these variants with other reported alkaline xylanases revealed silent mutations, some of which are due to codon preference in the respective organisms. The recombinant Xyl C1 that was successfully expressed in E. coli BL21 (DE3) had properties similar to the native enzyme.
Keywords: Alkaline xylanase C; Alkaliphilic Bacillus sp (NCL 87-6-10); Cloning; E. coli BL21 (DE3) expression; Sequence analysis